Late Fontan Circulatory Failure. What Drives Systemic Venous Congestion and Low Cardiac Output in Adult Fontan Patients? - Van De Bruaene, Alexander; Claessen, Guido; Salaets, Thomas; Gewillig, Marc (Frontiers in Cardiovascular Medicine, 2022)
The Fontan circulation provides definite palliation for children born with a single anatomical or functional ventricle by diverting systemic venous blood directly to the pulmonary arteries, effectively rendering systemic venous return into portal vessels to the lung. Although this restores pulmonary blood flow and avoids mixture of oxygenated and deoxygenated blood, it also results in elevated systemic venous pressures and low cardiac output. These are the 2 hallmarks of any Fontan circulation and the cause of Fontan circulatory failure later in life. We highlight the determinants of systemic venous return, its changed relationship with the pulmonary circulation, how it affects preload and the changed role of the heart (myocardium, valves and heart rate). By critically evaluating the components of the Fontan circulation, we hope to give some clues in how to optimize the Fontan circulation and avenues for future research.